Compiling Actions by Partial Evaluation, Revisited - Danvy, Olivier; Rhiger, Morten (BRICS Report Series, 1998)
We revisit Bondorf and Palsberg’s compilation of actions using< the offline syntax-directed partial evaluator Similix (FPCA’93, JFP’96), and we compare it in detail with using an online type-directed partial evaluator. In contrast to Similix, our type-directed partial evaluator is idempotent and requires no "binding-time improvements." It also appears to consume about 7 times less space and to be about 28 times faster than Similix, and to yield residual programs that are perceptibly more efficient than those generated by Similix.